Electronic speckle pattern interferometry and related techniques using digital still cameras - Abedin, K.M.; Haider, A F M Yusuf (© 2007 Nova Science Publishers, Inc., 2017)
This book chapter was published in the book Lasers, Optics and Electro-Optics Research Trends [© 2007 Nova Science Publishers, Inc.] and the definite version is available at: https://www.novapublishers.com/catalog/product_info.php?products_id=5662